The Relationship Between Interpersonal Ommunication Instructors With Learners’ Participation In The Dance Training Program At LKP Sanggar Permata Hati Padang City - Hanifa Zulmi; Setiawati Setiawati (Universitas Negeri Padang, 2022)
This research is motivated by the low participation of learning residents in the dance training program at the LKP Permata Hati Studio, Padang City, which is suspected to have something to do with interpersonal communication between instrukturs. The purpose of this study was to reveal a description of instruktur interpersonal communication, participation of learning residents in the Dance Training Program at LKP Permata Hati Studio, Padang City, and to reveal the relationship between instruktur interpersonal communication and the participation of learning residents in the dance training program at LKP Permata Hati Studio, Padang City. This type of research is a descriptive correlational research with a quantitative approach. The population of this study were residents learning dance training at the LKP Permata Hati Studio, Padang City in the 2019 period, totaling 34 people and a sample of 70%, namely 24 people with a sampling technique, namely cluster random sampling. The data collection technique used is a questionnaire and the tool used is a questionnaire. The data analysis technique used the percentage formula and the Spearman Rho formula. The results of this study indicate that: 1) the interpersonal communication of instrukturs in the dance training program at LKP Sanggar Permata Hati, Padang City is low; 2) the participation of the learning community in the dance training program at the LKP Permata Hati Studio, Padang City is relatively low; 3) there is a significant relationship between instruktur interpersonal communication and the participation of learning residents in the dance training program at LKP Permata Hati Studio, Padang City. Suggestions for this research are expected to the manager of LKP Permata Hati Padang City in order to encourage instrukturs to pay more attention to interpersonal, friendly and warm communication to learning residents in order to achieve learning objectives.